(untitled) (Research, Society and Development, 2021)
Introduction: suicidal behavior is a public health issue, therefore, it’s essential to offer resources for threats and support people suffering. Objective: to identify international smartphone app’s functionalities for the creation of a Brazilian smartphone app for the suicidal behavior prevention. Method: donwloading smartphone app’s, identifying functionalities manually, sending the functionalities found to specialists for evaluating evaluation of applicability in prototype smartphone app. Results and Discussion: of the 71 functionalities evaluated, 14 obtained 80% of the specialists’ consideration as suitable to the prototype. Of these, three were were considered suitable for 100% of the evaluators. Eight are self-managed care functionalities and 6 are shared management with services and /or health professionals. Conclusion: 14 functionalities were identified in the integrative literature review and consultation with experts in suicide prevention. Was indicated a model for further development of a smartphone app to prevent suicidal behavior in Brazil. Finally, it is recognized that this app may be part of future research on the prevention of suicidal behavior.